Ventricular Arrhythmia Precipitated by Severe Hypocalcaemia Secondary to Primary Hypoparathyroidism - S. Ashwin Reddy (Case Reports in Cardiology)
Hypocalcaemia causes neuromuscular and myocardial symptoms, including QT interval prolongation, and cardiac arrhythmias. Prompt detection and calcium replacement may reverse the pathology, following which the underlying cause should be diagnosed and treated to prevent recurrence. I present the case of a young man presenting with collapse who was found to have sinus rhythm with significant QT interval prolongation on admission electrocardiogram (ECG) associated with profound hypocalcaemia secondary to primary hypoparathyroidism.